Molecular characterization of the prevalent soil-transmitted helminths in Narathiwat Province, southern Thailand - Saiwasan Buathong; Nantana Suwandittakul; Musleeha Chesor; Piyaorn Chornchoem; Mathirut Mungthin (PLoS ONE, 2026)
Soil-transmitted helminths (STHs) are prevalent in tropical regions, including southern Thailand. However, limited data on their abundance in this area and molecular characteristics exist. This study evaluated 210 fecal specimens from the Narathiwat Province to determine the molecular profiles of STHs. Microscopic examination revealed that the predominant STHs were Trichuris spp. and Ascaris spp., with prevalences of 14.76% and 6.67%, respectively. Based on ITS1 sequencing, two haplotypes of Ascaris spp. were identified, classified as A . lumbricoides and A . suum . ITS1-based phylogeny revealed two distinct lineages: A . lumbricoides , which clustered with isolates from humans and primates, and A . suum , with genetic similarity to isolates from humans and animals. Classification based on the A. lumbricoides cox1 gene revealed five distinct haplotypes, including haplotype G, which exhibited high genetic similarity to A. suum isolates from pigs. In Trichuris spp., 18S rRNA sequencing identified four haplotypes that clustered with the reference isolates from humans and formed lineages distinct from the Trichuris spp. that infect animals. Analysis of the cox1 sequences of T. trichiura revealed four haplotypes clustering into distinct clades, which were genetically similar to reported human isolates but clearly differentiated from animal isolates. Pairwise F ST analysis revealed remarkable genetic variations within the populations of Ascaris and Trichuris spp., indicating potential species complexity. These findings provide valuable insights into the prevalence, genetic diversity, and molecular epidemiology of STHs in southern Thailand, which are vital for guiding further research to inform the control and prevention approaches in this endemic area.